1995
DOI: 10.1149/1.2050077
|View full text |Cite
|
Sign up to set email alerts
|

Hydrous Ruthenium Oxide as an Electrode Material for Electrochemical Capacitors

Abstract: The hydrous ruthenium oxide has been formed by a sol-gel process. The precursor was obtained by mixing aqueous solutions of RuC13 9 xH20 and alkalis. The hydrous ruthenium oxide powder was obtained by annealing the precursor at low temperatures. The crystalline structure and the electrochemical properties of the powder have been studied as a function of the annealing temperature. At lower annealing temperatures the powder is in an amorphous phase with a high specific capacitance. Specific capacitance as high a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

55
1,204
2
7

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,646 publications
(1,268 citation statements)
references
References 4 publications
55
1,204
2
7
Order By: Relevance
“…[55][56][57] More recently, attention has also focused on sol-gel techniques, which are reported to give fewer residual impurities and thus, enhanced service lifetimes. 50,[58][59][60][61] That said, the popularity of the thermal method is understandable given the ease with which oxide and, in particular, mixed oxide electrodes may be prepared. In this procedure a metal salt or a predetermined mix of metal salts in the desired stoichiometry are dissolved in a suitable solvent, often water or isopropanol, and the resulting solution is concentrated until a 'paste' consistency has been achieved.…”
Section: The Materials: Transition Metal Oxide Electrodesmentioning
confidence: 99%
“…[55][56][57] More recently, attention has also focused on sol-gel techniques, which are reported to give fewer residual impurities and thus, enhanced service lifetimes. 50,[58][59][60][61] That said, the popularity of the thermal method is understandable given the ease with which oxide and, in particular, mixed oxide electrodes may be prepared. In this procedure a metal salt or a predetermined mix of metal salts in the desired stoichiometry are dissolved in a suitable solvent, often water or isopropanol, and the resulting solution is concentrated until a 'paste' consistency has been achieved.…”
Section: The Materials: Transition Metal Oxide Electrodesmentioning
confidence: 99%
“…Such treatment would results in pore collapse, particle ripening, and loss of intra-particle water, in turn leading to smaller surface area and specific capacitance [43] [44]. The specific capacitance is unfortunately smaller than reported values for RuO 2 •nH 2 O prepared by sol-gel synthesis [25,26], most likely due to the larger primary particle size of RuO x (2 to 3 nm in diameter) constituting the walls and possible incomplete oxidation. Figure 1.…”
Section: Resultsmentioning
confidence: 91%
“…Takai et al have briefly reported on the synthesis of mesoporous Ru black with surface area of 62 m 2 g -1 via lyotropic crystal templating as the end member of the Pt-Ru alloy [23]. In addition to metallic Ru, high surface area ruthenium oxide is also an important material for various applications, including electrocatalysts for chlorine evolution [24], electrochemical capacitor electrodes [25][26][27][28][29], as well as fuel cell electrocatalysts [30][31][32][33][34][35][36][37][38][39]. The small particle size (1-2 nm) and the existence of appreciable pores are important requirements for the high capacitance [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudocapacitive materials, such as transition metal oxides/hydroxides and conducting polymers, are being explored for producing supercapacitors with increased specific capacitances (several times larger than those of carbonaceous materials) and high energy densities [2−6]. RuO 2 -base electrode materials are well studied as pseudocapacitive electrode materials with remarkable performance (760 F g −1 for a single electrode system) [7]. However, apart from being toxic, RuO 2 is quite expensive for extensive commercial applications.…”
mentioning
confidence: 99%